Activité Anthelminthique In Vitro Et Teneurs En Tanins Et Flavonoïdes De Huit Plantes Fourragères Utilisées En Elevage Des Petits Ruminants En Côte d’Ivoire - Mesmin, Koffi Yao; Kamelé, Kossonou Yao; Gervaise, Kouame Amoin; Jules, Kouadio N’Guessan; Adama, Bakayoko; Honora, Tra Bi Fézan; Witabouna, Kone Mamidou (European Scientific Journal, ESJ, 2018)
The search for alternatives to chemical anthelmintics in the control of gastrointestinal nematodes in small ruminants is now an imperative. the aim of this study was to evaluate the anthelmintic activity of eight forage plants from Côte d’Ivoire, including four Leguminosae and four Moraceae against Haemonchus contortus. The egg hatching inhibition and larvae paralysis were used for the assays. The contents of phenolic compounds (tannins and flavonoids) also were determined. Of the eight hydro-methanolic extracts prepared, three showed strong anthelmintic activity. The extract of Morus mesozygia was ovicidal (% inhibition = 84.08%), while that of Ficus lutea and Albizia adianthifolia were larvicidal (% mortality = 100% and 97.42% respectively) at 2 mg/mL. Tannins and flavonoids contents ranged between 1.60 and 2.89 mg catechol equivalent/g dry matter and 2.42 and 2.89 mg quercetin equivalent/g dry matter respectively. These three forage plants may be a good alternative in the control of gastrointestinal nematodes in small ruminants farming.